Financial performance-based assessment of companies’ competitiveness: Evidence from the Norwegian Shipbuilding Industry - Viktoriia Koilo; Antoni Vike Danielsen (Investment Management & Financial Innovations, 2023)
The Norwegian maritime industry is at the forefront of green technology development, with shipyards playing a crucial role in testing, verification, and development. However, the industry faces challenges such as high personal costs, increasing competition from abroad, and cyclical market trends. This study aims to assess financial performance as indicator of firm-level competitiveness based on a set of 12 financial measures and test the hypothesis of the positive impact of portfolio diversification on shipyards’ competitiveness.The analysis utilizes data from four large construction yards and four medium-sized construction, repair, and maintenance yards in the Møre region. The methodology involves constructing a Shipyard Competitiveness Index with sub-indices for liquidity, profitability, solvency, and efficiency. Regression analysis is conducted to investigate the impact of ship variety, as a diversification parameter, on the competitiveness level.The obtained results reveal that during the analyzed period (2009–2020), companies in the group of large shipyards had better financial performance until 2017, while on the contrary, the second group of shipyards in the same period showed an increase in their competitiveness index. Moreover, the findings proved the presence of the positive relationship between diversification of portfolio and competitiveness index.This study contributes valuable insights for the Norwegian shipbuilding industry, highlighting the importance of financial performance assessment in measuring competitiveness. The study provides a foundation for future discussions on fostering sustainable growth and innovation within the maritime sector.